Strategies of Sekolah Orang Tua Hebat in Enhancing Parenting Styles in the Digital Era - Herawati, Naila Nadda; Anggraini, Dite Mareta; Gunawan, Benny; Ikhrom, Annisa; Rosa, Adhysti Della; Siregar, Naomi Savannah; Sari, Dwi Astitie Indah; W, Stevie Menno Kristi; Canuri, Margrita Felania; S, Cindy Elga; Abror, Hadziqul (Universitas Lambung Mangkurat, 2025)
The Student Village Program aims to enhance the parenting skills of young parents in Jember Lor, Jember Regency, through the Sekolah Orang Tua Hebat (SOTH). This initiative focuses on parenting in the digital era, providing training and support through activities such as Focus Group Discussions (FGDs) and skill development workshops. The program was implemented using a combination of situation analysis, training sessions, and evaluations, which included surveys, site scouting, and obtaining the necessary permits to conduct activities at PAUD Alamanda 81. Key activities included pre-test and post-test assessments, interactive sessions, and the distribution of pocketbooks. The results demonstrated a significant improvement in parents' knowledge, attitudes, and skills related to parenting in the digital age, with pre-test and post-test scores indicating clear progress among participants. The program successfully fostered a positive digital parenting environment, contributing to the overall development of parenting knowledge. It also produced tangible outputs, such as media publications, social media engagement, and the creation of pocketbooks. The program enhanced the understanding of digital-era parenting among young mothers and fostered child growth in a more supportive environment. The findings and methodology of this program can serve as a model for similar initiatives in other areas, promoting the importance of effective parenting in the digital age.